The Effect of Work-Life Balance, Internal Communication, and Rewards on Employee Engagement and Employee Performance: A Study on Generation Z - Ambalika, Ni Komang Ayu Diah; Azzahra, Hurul A'ini Sekar; Rahmayanti, Putu Laksmita Dewi; Ditha, I Gusti Ayu Tara Laksemiyasa (International Journal of Business, Law, and Education, 2024)
The presence of a new workforce poses a potential challenge to the performance of the organization. This challenge arises due to differences and conflicts of values, needs, preferences and expectations among employees who come from four different generations, namely Baby Boomers, X, Y, and Z. Based on data from Good Stats, the Indonesian population is currently dominated by Generation Z where their work attitudes tend to be more unique than other generations so companies need to understand and adjust the needs of this dominating workforce. The purpose of this study is to analyze the influence of work-life balance, internal communication, and rewards, on employee engagement and employee performance of generation Z. The research was conducted using a quantitative method with a purposive sampling technique distributed to 226 respondents who were in the birth range of 1997 to 2012, had at least 1 year of work experience and are currently working as a permanent employee. This study uses Partial Least Square-Structural Equation Modelling analysis with SmartPLS software. Referring to the results of the analysis, it is known that work-life balance, internal communication, and rewards have a positive and significant effect on employee engagement, in addition to employee involvement has a positive and significant effect on the performance of generation Z employees.